A precessing Be disc as a possible model for occultation events in GX 304-1 - Kühnel, Matthias; Rothschild, R. E.; Okazaki, A. T.; Müller, Sebastian; Pottschmidt, K.; Ballhausen, Ralf; Choi, J.; Kreykenbohm, Ingo; Fuerst, F.; Marcu-Cheatham, D. M.; Hemphill, P.; Sagredo, Macarena; et al. (Monthly Notices of the Royal Astronomical Society, 2017)
We report on the RXTE detection of a sudden increase in the absorption column density, N-H, during the 2011 May outburst of GX 304-1. The NH increased up to similar to 16 x 10(22) atoms cm(-2), which is a factor of 3-4 larger than what is usually measured during the outbursts of GX 304-1 as covered by RXTE. Additionally, an increase in the variability of the hardness ratio as calculated from the energy resolved RXTE-Proportional Counter Array light curves is measured during this time range. We interpret these facts as an occultation event of the neutron star by material in the line of sight. Using a simple 3D model of an inclined and precessing Be disc around the Be-type companion, we are able to qualitatively explain the NH evolution over time. We are able to constrain the Be disc density to be of the order of 10(-11) g cm(-3). Our model strengthens the idea of inclined Be discs as origin of double-peaked outbursts as the derived geometry allows accretion twice per orbit under certain conditions.
Keywords: occultations; stars: neutron; pulsars: individual: GX 304-1; X-rays: binaries

GRO J1008-57: an (almost) predictable transient X-ray binary - Kühnel, Matthias; Müller, Sebastian; Kreykenbohm, Ingo; Fuerst, F.; Pottschmidt, K.; Rothschild, R. E.; Caballero, I.; Grinberg, Victoria; Schoenherr, G.; Shrader, C.; Klochkov, D.; Staubert, R.; et al. (Astronomy & Astrophysics, 2013)
A study of archival RXTE, Swift, and Suzaku pointed observations of the transient high-mass X-ray binary GRO J1008-57 is presented. A new orbital ephemeris based on pulse arrival-timing shows the times of maximum luminosities during outbursts of GRO J1008-57 to be close to periastron at orbital phase -0.03. This makes the source one of a few for which outburst dates can be predicted with very high precision. Spectra of the source in 2005, 2007, and 2011 can be well described by a simple power law with high-energy cutoff and an additional black body at lower energies. The photon index of the power law and the black-body flux only depend on the 15-50 keV source flux. No apparent hysteresis effects are seen. These correlations allow us to predict the evolution of the pulsar's X-ray spectral shape over all outbursts as a function of just one parameter, the source's flux. If modified by an additional soft component, this prediction even holds during GRO J1008-57's 2012 type II outburst.
Keywords: X-rays: binaries; pulsars: individual: GRO J1008-57; accretion; accretion disks; ephemerides

Hot subdwarf stars in close-up view: I. Rotational properties of subdwarf B stars in close binary systems and nature of their unseen companions - Geier, Stephan; Heber, Ulrich; Podsiadlowski, Ph.; Edelmann, Heinz; Napiwotzki, R.; Kupfer, Thomas; Müller, Sebastian (Astronomy & Astrophysics, 2010)
The origin of hot subdwarf B stars (sdBs) is still unclear. About half of the known sdBs are in close binary systems for which common envelope ejection is the most likely formation channel. Little is known about this dynamic phase of binary evolution. Since most of the known sdB systems are single-lined spectroscopic binaries, it is difficult to derive masses and unravel the companions' nature, which is the aim of this paper. Due to the tidal influence of the companion in close binary systems, the rotation of the primary becomes synchronised to its orbital motion. In this case it is possible to constrain the mass of the companion, if the primary mass, its projected rotational velocity as well as its surface gravity are known. For the first time we measured the projected rotational velocities of a large sdB binary sample from high resolution spectra. We analysed a sample of 51 sdB stars in close binaries, 40 of which have known orbital parameters comprising half of all such systems known today. Synchronisation in sdB binaries is discussed both from the theoretical and the observational point of view. The masses and the nature of the unseen companions could be constrained in 31 cases. We found orbital synchronisation most likely to be established in binaries with orbital periods shorter than 1.2 d. Only in five cases it was impossible to decide whether the sdB's companion is a white dwarf or an M dwarf. The companions to seven sdBs could be clearly identified as late M stars. One binary may have a brown dwarf companion. The unseen companions of nine sdBs are white dwarfs with typical masses. The mass of one white dwarf companion is very low. In eight cases (including the well known system KPD1930+2752) the companion mass exceeds 0.9∼M-, four of which even exceed the Chandrasekhar limit indicating that they may be neutron stars. Even stellar mass black holes are possible for the most massive companions. The distribution of the inclinations of the systems with low mass companions appears to be consistent with expectations, whereas a lack of high inclinations becomes obvious for the massive systems. We show that the formation of such systems can be explained with common envelope evolution and present an appropriate formation channel including two phases of unstable mass transfer and one supernova explosion. The sample also contains a candidate post-RGB star, which rotates fast despite its long orbital period. The post-RGB stars are expected to spin-up caused by their ongoing contraction. The age of the sdB is another important factor. If the EHB star is too young, the synchronisation process might not be finished yet. Estimating the ages of the target stars from their positions on the EHB band, we found PG 2345+318, which is known not to be synchronised, to lie near the zero-age extreme horizontal branch as are the massive candidates PG 1232-136, PG 1432+159 and PG 1101+249. These star may possibly be too young to have reached synchronisation. The derived large fraction of putative massive sdB binary systems in low inclination orbits is inconsistent with theoretical predictions. Even if we dismiss three candidates because they may be too young and assume that the other sdB primaries are of low mass, PG 1743+477 and, in particular, HE 0532-4503 remain as candidates whose companions may have masses close to or above the Chandrasekhar limit. X-ray observations and accurate photometry are suggested to clarify their nature. As high inclination systems must also exist, an appropriate survey has already been launched to find such binaries. © 2010 ESO.
CRIS-Team Scopus Importer:2020-12-21
Keywords: Binaries: spectroscopic; stars: rotation; subdwarfs

Luminosity dependent accretion state change in GRO J1008-57 - Kühnel, Matthias; Müller, Sebastian; Kreykenbohm, Ingo; Fuerst, Felix; Pottschmidt, Katja; Rothschild, Richard E.; Caballero, Isabel; Grinberg, Victoria; Schoenherr, Gabriele; Shrader, Chris; Klochkov, Dmitry; Staubert, Ruediger; et al. (2014)
In a former publication, we have analyzed the transient neutron star X-ray binary GRO J1008-57 using all available RXTE-, Swift-, and Suzaku-data. As we have found, the source's spectral components, i.e., a power-law with high exponential cutoff and a black-body, are strongly correlated with the hard X-ray flux (15-50 keV). We update the analytical description of these dependence, including a change in the photon index behaviour from a flat to a logarithmic function. The flux, where the change occurs, is consistent with the onset of the black-body emission. Thus, a change of the accretion state always occurs in GRO J1008-57 at a particular flux level.

MUCHFUSS - Massive Unseen Companions to Hot Faint Underluminous Stars from SDSS - Geier, Stephan; Schaffenroth, Veronika; Hirsch, H.; Tillich, A.; Heber, Ulrich; Maxted, P. F. L.; Ostensen, R. H.; Barlow, B. N.; O'Toole, S. J.; Kupfer, Thomas; Marsh, T.; Gaensicke, Boris T; et al. (Astronomische Nachrichten, 2012)
The project Massive Unseen Companions to Hot Faint Underluminous Stars from SDSS (MUCHFUSS) aims at finding hot subdwarf stars with massive compact companions (white dwarfs with masses M > 1.0 M ⊙, neutron stars or black holes). The existence of such systems is predicted by binary evolution calculations and some candidate systems have been found. We identified ≃1100 hot subdwarf stars from the Sloan Digital Sky Survey (SDSS). Stars with high velocities have been reobserved and individual SDSS spectra have been analysed. About 70 radial velocity variable subdwarfs have been selected as good candidates for follow-up time resolved spectroscopy to derive orbital parameters and photometric follow-up to search for features like eclipses in the light curves. Up to now we found nine close binary sdBs with short orbital periods ranging from ≃0.07 d to 1.5 d. Two of them are eclipsing binaries with companions that are most likely of substellar nature © 2012 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.
CRIS-Team Scopus Importer:2020-12-21
Keywords: Binaries: spectroscopic; Subdwarfs

No anticorrelation between cyclotron line energy and X-ray flux in 4U 0115+634 - Müller, Sebastian; Ferrigno, C.; Kühnel, Matthias; Schoenherr, G.; Becker, P. A.; Wolff, M. T.; Hertel, Dominik; Schwarm, Fritz-Walter; Grinberg, Victoria; Obst, M.; Caballero, I.; Pottschmidt, K.; et al. (Astronomy & Astrophysics, 2013)
We report on an outburst of the high mass X-ray binary 4U 0115+634 with a pulse period of 3.6 s in 2008 March/April as observed with RXTE and INTEGRAL. During the outburst the neutron star's luminosity varied by a factor of 10 in the 3-50 keV band. In agreement with earlier work we find evidence of five cyclotron resonance scattering features at similar to 10.7, 21.8, 35.5, 46.7, and 59.7 keV. Previous work had found an anticorrelation between the fundamental cyclotron line energy and the X-ray flux. We show that this apparent anticorrelation is probably due to the unphysical interplay of parameters of the cyclotron line with the continuum models used previously, e. g., the negative and positive exponent power law (NPEX). For this model, we show that cyclotron line modeling erroneously leads to describing part of the exponential cutoff and the continuum variability, and not the cyclotron lines. When the X-ray continuum is modeled with a simple exponentially cutoff power law modified by a Gaussian emission feature around 10 keV, the correlation between the line energy and the flux vanishes, and the line parameters remain virtually constant over the outburst. We therefore conclude that the previously reported anticorrelation is an artifact of the assumptions adopted in the modeling of the continuum.
Keywords: X-rays: binaries; pulsars: individual 4U 0115+634; magnetic fields

Staring at 4U 1909+07 with Suzaku - Fürst, Felix; Pottschmidt, K.; Kreykenbohm, Ingo; Müller, Sebastian; Kühnel, Matthias; Wilms, Jörn; Rothschild, R. E. (Astronomy & Astrophysics, 2012)
We present an analysis of the neutron star high mass X-ray binary (HMXB) 4U 1909+07 mainly based on Suzaku data. We extend the pulse period evolution, which behaves in a random-walk like manner, indicative of direct wind accretion. Studying the spectral properties of 4U 1909+07 between 0.5 to 90 keV we find that a power-law with an exponential cutoff can describe the data well, when additionally allowing for a blackbody or a partially covering absorber at low energies.We find no evidence for a cyclotron resonant scattering feature (CRSF), a feature seen in many other neutron star HMXBs sources. By performing pulse phase resolved spectroscopy we investigate the origin of the strong energy dependence of the pulse profile, which evolves from a broad two-peak profile at low energies to a profile with a single, narrow peak at energies above 20 keV. Our data show that it is very likely that a higher folding energy in the high energy peak is responsible for this behavior. This in turn leads to the assumption that we observe the two magnetic poles and their respective accretion columns at different phases, and that these accretion columns have slightly different physical conditions.
Keywords: accretion; accretion disks; X-rays: binaries; stars: neutron

THE 5 hr PULSE PERIOD AND BROADBAND SPECTRUM OF THE SYMBIOTIC X-RAY BINARY 3A 1954+319 - Marcu, Diana M.; Fürst, Felix; Pottschmidt, Katja; Grinberg, Victoria; Müller, Sebastian; Wilms, Jörn; Postnov, Konstantin A.; Corbet, Robin H. D.; Markwardt, Craig B.; Cadolle Bel, Marion (Astrophysical Journal Letters, 2011)
We present an analysis of the highly variable accreting X-ray pulsar 3A 1954 + 319 using 2005-2009 monitoring data obtained with INTEGRAL and Swift. This considerably extends the pulse period history and covers flaring episodes in 2005 and 2008. In 2006 the source was identified as one of only a few known symbiotic X-ray binaries (SyXBs), i.e., systems composed of a neutron star accreting from the inhomogeneous medium around an M-giant star. The extremely long pulse period of similar to 5.3 hr is directly visible in the 2008 INTEGRAL-ISGRI outburst light curve. The pulse profile is double peaked and generally not significantly energy dependent although there is an indication of possible softening during the main pulse. During the outburst a strong spin-up of -1.8 x 10(-4) hr hr(-1) occurred. Between 2005 and 2008 a long-term spin-down trend of 2.1 x 10(-5) hr hr(-1) was observed for the first time for this source. The 3-80 keV pulse peak spectrum of 3A 1954 + 319 during the 2008 flare could be well described by a thermal Comptonization model. We interpret the results within the framework of a recently developed quasi-spherical accretion model for SyXBs.
Keywords: binaries: symbiotic; stars: individual (3A 1954+319); stars: neutron; X-rays: binaries

The giant outburst of 4U 0115+634 in 2011 with Suzaku and RXTE: Minimizing cyclotron line biases - Kühnel, Matthias; Kreykenbohm, Ingo; Ferrigno, Carlo; Pottschmidt, Katja; Marcu-Cheatham, Diana M.; Fuerst, Felix; Rothschild, Richard E.; Kretschmar, Peter; Klochkov, Dmitry; Hemphill, Paul; Hertel, Dominik; Müller, Sebastian; et al. (Astronomy & Astrophysics, 2020)
We present an analysis of X-ray spectra of the high-mass X-ray binary 4U 0115+634 as observed with Suzaku and RXTE in 2011 July, during the fading phase of a giant X-ray outburst. We used a continuum model consisting of an absorbed cutoff power law and an ad hoc Gaussian emission feature centered around 8.5 keV, which we attribute to cyclotron emission. Our results are consistent with a fundamental cyclotron absorption line centered at similar to 10.2 keV for all observed flux ranges. At the same time we rule out significant influence of the 8.5 kev Gaussian on the parameters of the cyclotron resonant scattering feature, which are not consistent with the cyclotron line energies or the depths of previously reported flux-dependent descriptions. We also show that some continuum models can lead to artificial line-like residuals in the analyzed spectra, which are then misinterpreted as unphysically strong cyclotron lines. Specifically, our results do not support the existence of a previously claimed additional cyclotron feature at similar to 15 keV. Apart from these features, we find for the first time evidence for a He-like FeXXV emission line at similar to 6.7 keV and weak H-like FeXXVI emission close to similar to 7.0 keV.
CRIS-Team WoS Importer:2020-03-13

The reawakening of the sleeping X-ray pulsar XTE J1946+274 - Müller, Sebastian; Kühnel, Matthias; Caballero, I.; Pottschmidt, K.; Fürst, Felix; Kreykenbohm, Ingo; Sagredo, Macarena; Obst, M.; Wilms, Jörn; Ferrigno, C.; Rothschild, R. E.; Staubert, R. (Astronomy & Astrophysics, 2012)
We report on a series of outbursts of the high-mass X-ray binary XTE J1946+274 in 2010/2011 observed with INTEGRAL, RXTE, and Swift. We discuss possible mechanisms resulting in the extraordinary outburst behavior of this source. The X-ray spectra can be described by standard phenomenological models, enhanced by an absorption feature of unknown origin at about 10 keV and a narrow iron K alpha fluorescence line at 6.4 keV, which are variable in flux and pulse phase. We find possible evidence for a cyclotron resonance scattering feature at about 25 keV at the 93% level. The presence of a strong cyclotron line at 35 keV seen in data from the source's 1998 outburst that was confirmed by a reanalysis of these data can be excluded. This result indicates that the cyclotron line feature in XTE J1946+274 is variable between individual outbursts.
Keywords: X-rays: binaries; accretion; accretion disks

THE TRANSIENT ACCRETING X-RAY PULSAR XTE J1946+274: STABILITY OF X-RAY PROPERTIES AT LOW FLUX AND UPDATED ORBITAL SOLUTION - Marcu-Cheatham, Diana M.; Pottschmidt, Katja; Kühnel, Matthias; Müller, Sebastian; Falkner, Sebastian; Caballero, Isabel; Finger, Mark H.; Jenke, Peter J.; Wilson-Hodge, Colleen A.; Fuerst, Felix; Grinberg, Victoria; Hemphill, Paul B.; et al. (Astrophysical Journal, 2015)
We present a timing and spectral analysis of the X-ray pulsar XTE J1946+274 observed with Suzaku during an outburst decline in 2010 October and compare with previous results. XTE J1946+274 is a transient X-ray binary consisting of a Be-type star and a neutron star with a 15.75 s pulse period in a 172 days orbit with 2-3 outbursts per orbit during phases of activity. We improve the orbital solution using data from multiple instruments. The X-ray spectrum can be described by an absorbed Fermi-Dirac cut-off power-law model along with a narrow Fe K alpha line at 6.4 keV and a weak Cyclotron Resonance Scattering Feature (CRSF) at similar to 35 keV. The Suzaku data are consistent with the previously observed continuum flux versus iron line flux correlation expected from fluorescence emission along the line of sight. However, the observed iron line flux is slightly higher, indicating the possibility of a higher iron abundance or the presence of non-uniform material. We argue that the source most likely has only been observed in the subcritical (non-radiation dominated) state since its pulse profile is stable over all observed luminosities and the energy of the CRSF is approximately the same at the highest (similar to 5 x 10(37) erg s(-1)) and lowest (similar to 5. x 10(36) erg s(-1)) observed 3-60 keV luminosities.
Keywords: accretion; accretion disks; pulsars: individual (XTE J1946+274); X-rays: binaries